2013
DOI: 10.5812/numonthly.14087
|View full text |Cite
|
Sign up to set email alerts
|

Overactive Bladder Syndrome and the Potential Role of Prostaglandins and Phosphodiesterases: An Introduction

Abstract: In this paper, a general introduction is given, presenting the overactive bladder syndrome (OAB) and its impact on the quality of life and economical burden in patients affected. Moreover, the anatomy, physiology and histology of the lower urinary tract are discussed, followed by a brief overview on the possible role of prostaglandin (PG) and phosphodiesterase type 5 (PDE5) in the urinary bladder. The current literature on the role and distribution of PGE2 and its receptors in the urinary bladder is discussed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 118 publications
0
18
0
Order By: Relevance
“…PG synthesis is initiated by several factors, as follow: 1) detrusor muscle stretching, 2) urinary bladder autonomic nerve fibers stimulation, 3) urinary bladder mucosal damage, and 4) inflammatory mediators (e.g. due to neurogenic inflammation) [5]. Numerous studies describing the effects of PGs in the urinary bladder have been published.…”
mentioning
confidence: 99%
“…PG synthesis is initiated by several factors, as follow: 1) detrusor muscle stretching, 2) urinary bladder autonomic nerve fibers stimulation, 3) urinary bladder mucosal damage, and 4) inflammatory mediators (e.g. due to neurogenic inflammation) [5]. Numerous studies describing the effects of PGs in the urinary bladder have been published.…”
mentioning
confidence: 99%
“…Several investigators have shown that IC exist within DSM bundles of various mammalian species [79]. Previous work with rabbit DSM suggests that cyclooxygenase-mediated signaling between IC and adjacent DSM bundles may play a role in the generation of LARC via prostaglandin signaling with these findings supporting the fact that increased prostaglandin levels are seen in patients with OAB-type symptoms [24]. Others have shown that urinary bladder IC generate calcium transients that have similar frequencies to those observed in the current study suggesting IC within the bladder may be a potential source for an intrinsic bladder pacemaker [9,10].…”
Section: Discussionmentioning
confidence: 88%
“…GFP-tagged P2X3 was constructed by subcloning the full-length P2X3 cDNA into a pEGFP-N2 vector (Clontech). HA-tagged Pirt and PirtD (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) were constructed by subcloning the full-length or truncated Pirt cDNA into the pCMV-HA vector (Clontech). Full-length P2X3 cDNA was also subcloned into pcDNA3.1 3.1/myc-His( À ) A (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…In response to physical and chemical stimulation, the urothelium releases several substances, including acetylcholine, ATP, prostaglandins and so on [6][7][8] . These chemical agents modify afferent nerve activity and sensation in the suburothelial layer and in the muscle layer 2 .…”
mentioning
confidence: 99%